Obesity, gestational weight gain, and birth weight in women with gestational diabetes : the LINDA-Brasil (2014-2017) and the EBDG (1991-1995) studies - Silveira, Letícia Ribeiro Pavão da (2021)
Objective: This study aimed to evaluate gestational weight gain and birth weight in women with gestational diabetes mellitus of two Brazilian cohorts enrolled three decades apart. Methods: The authors compared data of 2362 women from the Lifestyle INtervention for Diabetes Prevention After Pregnancy study (LINDA-Brasil, 2014-2017) to those of 359 women from the Estudo Brasileiro de Diabetes Gestacional study (EBDG, 1991-1995). Gestational weight gain was classified by the 2009 Institute of Medicine criteria; large and small for gestational age newborns, by the Intergrowth-21st chart. Differences in birth weight means between pregestational BMI and gestational weight gain categories were evaluated by ANOVA; the associations of gestational weight gain and birth weight, through multivariable Poisson regression. Results: In LINDA-Brasil, women presented higher pregestational body mass index (30.3 ± 6.5 vs. 24.6 ± 4.4 kg/m2) and were frequently obese (46.4 vs. 11.1%) compared to those of the EBDG. In the EBDG, gestational weight gain was larger (11.3 ± 6.1 vs. 9.2 ± 7.6 kg) and rates of small for gestational age higher (7.5 vs. 4.5%) compared to LINDA-Brasil. In LINDA-Brasil, excessive gestational weight gain was associated to macrosomia (adjusted relative risk [aRR]: 1.59, 95% CI 1.08-2.35) and large for gestational age (aRR: 1.40; 95% CI 1.05-1.86); less gain increased the risk of low birth weight (aRR: 1.66; 95% CI 1.05-2.62) and small for gestational age (aRR: 1.79; 95% CI 1.03-3.11). These associations were similar in the EBDG, although not statistically significant. Conclusions: Improvements in gestational weight gain and rates of small for gestational age occurred over time in gestational diabetes mellitus pregnancies, accompanied by a worsening in maternal weight profile. This highlights the nutritional transition during this period and the importance of avoiding excessive gestational weight gain as well as promoting adequate weight before conception.